The Feast of the Road Cross - Mumbai Archive Project Team (Jio Institute, 2024)
The Feast of the Road Cross is celebrated annually on May 31, commemorating the visitation of the Blessed Virgin Mary. In Catholic Christianity, the visitation recounts the encounter in the New Testament when the pregnant Virgin Mary visits her cousin Elizabeth, who is pregnant with John the Baptist. This event is described in the Gospel of Luke 1:39–56.